THE DNA-DIAGNOSTICS FORM CONGENITAL ADRENAL HYPERPLASIA CHILDREN - V. V. Grigoryan; V. A. Shashil; S. A. Matulevich (Кубанский научный медицинский вестник)
In 2013 in territory Regional clinical hospital № 1 by him. prof. S. V. Ochapovskiy, Kuban interregional medico-genetic advice on program was examined 68 501 newborns. The method of research is to define 17aoksigidroprogesteron levei by immunofiuorescent analyses and CYP-21. The frequency of disease is 1:8069 of newborns. The eariy diagnoses of disease prevent the childrens death from solwasting crisis and encourage the correct choice of sexual characteristics in verilization of girls external genitalis.